Evaluation of the Potential Contributions of Transition to Digital Product Passports in the Electric Vehicle Sector to Circular Supply Chain Processes (Third Sector Social Economic Review, 2026)
ABSTRACTThe production and use of batteries and other critical components in the electric vehicle sector creates significant environmental and economic impacts. In this context, digital product passports provide information such as product material composition, usage history, and recovery potential, enabling the effective management of resources throughout the supply chain and their allocation to recycling processes. The study evaluated the contributions of the transition to digital product passports to circular supply chain processes using the Intuitionistic Fuzzy Step-Wise Weight Assessment Ratio Analysis (SWARA) method. According to the research findings, the "information technology investments/digital maturity" criterion received the highest weighting, with 5.16%, while the "reverse logistics" criterion received the lowest weighting, with 4.78%. It is considered that digital product passports, through the transparency and traceability they provide, will enhance the effectiveness of sustainable supply chains in trade and international logistics processes with the European Union and play a critical role in strategic planning and the achievement of sustainability goals in the electric vehicle sector.
Keywords: Digital Product Passport; Circular Supply Chain; International Trade; Logistics; Fuzzy Decision Making